EFFECT OF RED DRAGON FRUIT EXTRACT (HYLOCEREUS POLYRHIZUS) ON VAGINAL EPITHEL THICKNESS IN MENOPAUSE RAT MODEL - Suwitari, Diah Ayu; Sugiritama, I Wayan; Ratnayanti, I Gusti Ayu Dewi; Wahyuniari, Ida Ayu Ika (E-Jurnal Medika Udayana, 2024)
Background: Menopause is a condition where estrogen levels decline in women. Menopause can cause thinning of the vaginal epithelium. This is mediated by two pathways which are decreasing estrogen function and oxidative stress. Flavonoid compounds, anthocyanins, and tannins found in Hylocereus Polyrhizus peel are reported to have phytoestrogens and antioxidants activities, thus have potential to improve vaginal atrophy. Objective: This study aims to determine whether menopausal rats given ethanol extract of Hylocereus Polyrhizus fruit peel had higher epithelial thickness than controls. Methods: This research is an in vivo study with experimental post test only design with control group. This study used menopausal rats as subjects who were given ethanol extract of Hylocereus Polyrhizus peel to assess its effect on vaginal epithelial thickness. 30 wistar rats were divided into three groups, namely the control group (P0), intervention group of 60mg/200grBB (P1), and intervention group of 90mg/200grBB (P2). Subjects were given intervention for 30 days then terminated and their vaginal organs was retrieved. The caginal epithelial thickness (?m) was measured by using ImageJ. All data obtained were analyzed statistically with SPSS ver. 20. Results: The mean thickness of the epithelium at P0, P1, and P2 was 54.51±16.92 ?m; 66.91±17.12 ?m; 85.32±19.49 ?m respectively. One Way ANOVA test found that there were statistically significant differences among groups (p = 0.005). There were significant differences in the mean thickness of the vaginal epithelium between P0 and P2; and P1 and P2 (p = 0.001). However, there was no significant difference between P0 and P1 (p = 0.154). Conclusion: The mean thickness of the vaginal epithelium in menopausal model rats by administration of ethanol extract from the peel of red dragon fruit (Hylocereous Polyrhizus) was higher than the control. The highest vaginal epithelial thickness was found at P2. Keywords : phytoestrogens, antioxidants, Hylocereus Polyrhizus, vaginal epithelium, menopause